Analysis of power system stability using prony analysis / Arfah Marini Mohamad - Mohamad, Arfah Marini (2017)
A good power system analysis is measured through the ability to detect response after experiencing disturbance within a specified requirement in a fastest way. In this manner, more condition can be implemented and analyzed to detect the possibility of instability that could lead to system collapse. Difficulty to detect the stability of a large power system network is due to simulation test produces up to thousands of output signal. Since the power system network grows each year, the simulation test of system stability should be performed each time the network changes in order to ensure the system adequacy and security are fulfilled. Furthermore, system stability test involves a lot of elements, where each of them need to be thoroughly examined, thus it is time consuming. This paper examines signal stability through its damping ratio, computes by a digital signal processing method named Prony analysis. Prony analysis will produces an output of amplitude, damping coefficient and frequency from an output signal as the components to calculate damping ratio. The calculation of damping ratio used as an indicator in achieving compliance with the limit specified by the Malaysian planning standards. Multiple software was used base on simulation and analysis among them are spreadsheet (Microsoft Excel), simulation (Power System Simulator for Engineer - PSSE) and analysis (MATLAB) are integrated together to dynamically screen several PSSE simulated output signal files consist of various elements at one instance to speed up analysis.